Infrastructure and rurality: Challenges for sustainable economic development in Latin America (2020)
Latin America is a region with a great environmental and cultural diversity; however, most of its countries have high levels of poverty and inequality, characteristics that are accentuated in rural areas. This paper establishes that the reduction of the urban-rural gap and investment in sustainable infrastructure are the key challenges facing Latin American governments to achieve significant progress. The analysis explains that, if infrastructure projects are promoted in the region, it impacts on at least nine sustainable development goals (SDGs), which would result in a significant increase in people's well-being.